Manual Transplanting vs. Mechanical Transplanting of Paddy: A Techno-economic Analysis in Assam - Baruah, D C; Goswami, N G; Saikia, R (Journal of Agricultural Engineering, 2001)
Performance of an eight-row self propelled paddy transplanter with respect to the technological feasibility, economic merits, and energetics was compared with manual transplanting. Field trials on the transplanter were conducted in two selected districts of Assam and total area of 5.0 ha was covered. Improper leveling of the land, elevated bunds in between plots, soft patches of land at certain points and leftover debris and stubbles from the previous crop were found to be some of the hindrances affecting the machine operation. Cost of machine transplanting was found to be only Rs. 1310/ha in comparison to Rs. 2463/ha for manual transplanting. The cost of growing mat type nursery for mechanical transplanting was about 40 percent whereas the cost for raising conventional nursery was only 25 percent of the cost of transplanting. The energy requirements for mechanical and manual methods of transplanting were found to be 1074 and 757 MJ/ha, respectively. Forty percent of the total energy requirement in mechanical transplanting was required in mat nursery preparation while energy share for traditional nursery under manual transplanting was only 11 %. The average number of hills planted per mÂ² by the transplanter was 31 with four numbers of plants per hill. The yield of mechanically transplanted paddy was found to vary from 3.75 t/ha to 5.70 t/ha with an average yield of 4.71 t/ha. Average yield in manually transplanted paddy was 4.50 t/ha.